A Model for Investigating Sources of Li-Ion Battery Electrode Heterogeneity: Part I. Electrode Drying and Calendering Processes. Issue 6 (24th June 2021) - Nikpour, M.; Barrett, N.; Hillman, Z.; Thompson, A. I.; Mazzeo, B. A.; Wheeler, D. R.
Abstract : Heterogeneity of porous electrodes can cause battery failure and performance deficiencies. On the other hand, some types of heterogeneity can improve performance. This study uses a multi-phase smoothed particle (MPSP) model, derived from smoothed particle hydrodynamics (SPH) and which is parameterized and validated by comparison with experimental viscosity, density, electronic conductivity, MacMullin number, and Young's modulus of electrode films. The MPSP model simulates all major aspects of electrode production: mixing, coating, drying, and calendering, though the focus in this paper (Part 1) is on drying and calendering. Four types of electrodes are included in this study: a graphite anode and three traditional metal oxide cathodes. The model suggests how some types of heterogeneity can form during cathode and anode fabrication. The anode is more susceptible to mesoscale heterogeneities than the cathode due to differences in active particle shape and stiffness. The model and experiments show that regardless of the active material type, calendering increases the variability in electronic and ionic conductivity due to carbon and binder redistribution. This can be explained by means of the proposed multi-phase packing theory. On the other hand, calendering increases mechanical uniformity as also shown by model and experiment.